Excitonic states and energy relaxation in low‐dimension CdSe/ZnSe structures with isolated ZnCdSe islands. Issue 8 (9th March 2015) - Reznitsky, A.; Eremenko, M.; Sedova, I. V.; Sorokin, S. V.; Ivanov, S. V.
<x xml:space="preserve">Abstract</x> Photoluminescence (PL) and PL excitation (PLE) spectra of structures containing MBE‐grown CdSe layers with a nominal thickness tCdSe of 1.4–2.7 monolayers (MLs) in a ZnSe matrix have been studied. It is shown that the main features of the PLE spectra in structures with different amounts of deposited CdSe can be described in terms of two different models: in structures with tCdSe exceeding approximately 1.7 ML, the properties of electronic states correspond to the frequently used model of the quantum well formed by an inhomogeneous ZnCdSe solid solution with nanosize inclusions constituted by planar ZnCdSe islands whose composition is strongly enriched with CdSe, whereas the properties of electronic states in structures with tCdSe < 1.6 ML can be described in the model of isolated uncoupled ZnCdSe nanoislands. It was found that the main channel by which emitting states are occupied under excitation with photons in a wide energy range both in the region of quantum‐dot states and in that of free states in the ZnSe barrier is the cascade relaxation of hot excitons, with emission of longitudinal optical phonons. Other properties of electronic states in nano‐objects of this kind are discussed.